1998
DOI: 10.1046/j.1365-2168.1998.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy and laparoscopy differentially accelerate experimental flank tumour growth

Abstract: Extraperitoneal tumour growth was significantly accelerated after laparotomy and correlated with significantly suppressed NK and LAK cytotoxicity for at least 4 days after operation. Laparoscopy had a shorter, less profound effect on tumour growth and immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 32 publications
3
71
3
1
Order By: Relevance
“…In addition, removal of the primary tumour, a source of the endogenous angiogenesis inhibitor, angiostatin, may remove a 'brake' on metastatic growth (O'Reilly et al, 1997). Previously, we have shown that the surgical insult accelerates the growth of the primary tumour and increases pulmonary metastases (Da Costa et al, 1998;Pidgeon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, removal of the primary tumour, a source of the endogenous angiogenesis inhibitor, angiostatin, may remove a 'brake' on metastatic growth (O'Reilly et al, 1997). Previously, we have shown that the surgical insult accelerates the growth of the primary tumour and increases pulmonary metastases (Da Costa et al, 1998;Pidgeon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In most cancer patients, metastases are already present at time of diagnosis (Fidler and Ellis, 1994) and while surgery remains the mainstay of treatment for primary tumours it may paradoxically enhance growth of residual or metastatic disease (Da Costa et al, 1998;Pidgeon et al, 1999;Demichelli et al, 2001). This may occur as a consequence of an alteration in the balance between pro-and antiangiogenic factors as part of the healing process and removal of the tumour can of itself stimulate tumour growth by removing the source of angiostatin (O'Reilly et al, 1997).…”
mentioning
confidence: 99%
“…Extensive clinical and experimental evidence indicates that tumor removal adversely alters the growth kinetics of residual neoplasia (11)(12)(13)(14)(15)(16)(17)(18). Tumor cell proliferation is increased in local tumor recurrences following curative-intent excisional surgery (3,7).…”
mentioning
confidence: 99%
“…Hence, any disruption of immune function as a result of surgery can also lead to potentiating tumour growth. Interestingly, this immuno-suppression is greater dependent on the extent of surgery (Da Costa, 1998;. The immunosuppressive effects of surgery can last anywhere from between 4 to 14 days depending on the size of surgical trauma induced but peaks day three post-operatively in most cases.…”
Section: Mechanisms Of Surgery Induced Tumourigenesismentioning
confidence: 99%